Preliminary Plant Design Of Chloroform From Acetone And Bleaching Powder Capacity 19,000 Tonnes Per Year - QOMAROH, Qomaroh, M. Mujiburohman, S.T., M.T., Ph.D, Emi Erawati, S.T., M.Eng (2014)
Indonesia still has not built any chloroform plants. To meet the need of society for chloroform, Indonesia is still importing from other countries. The plant capacity is then determined to reach 19,000 tonnes/year in Cilegon, Banten. Chloroform is produced by reactions acetone 1307.300 kg/year and bleaching powder 13073.002 kg/year. Using reactor which is equiped with agitator at temperature 50℃ and pressure 1 atm also 2 hours for reaction. Besides being the main product, chloroform within reactor also produces calcium acetate Ca(CH3COO)2, calcium hydroxide (Ca(OH)2), calcium chloride (CaCl2). With area of plant 38,857 m2, total of water needs is 147 m3/hours, steam required is 2,506.886 kg/h, for electricity is 529 KW, fuel requirement is 82.79 L/h, this plant will start to produce in 2015. The economic analysis concludes that fixed manufacturing cost (Fa) is 462,493,237,829. Variable cost (Va) is 7,852,508,693,058. Regulated cost (Ra) is 7,941,777,516,246. Selling product (Sa) is 19,629,796,640,852. ROI (Return on Investment) before and after tax is 94.811% and 66.36%. POT (Pay Out Time) before and after tax is 0.95 years and 1.31 years. BEP (Break-even Point) 45.75%, and SDP (Shutdown Point) 38.32%. While DCF (Discounted Cash Flow) as 35.61%. From the economic analysis, this plant is recommended to build.